Kajian Biologi Reproduksi Ikan Nila Jatimbulan (Oreochromis niloticus) Melalui Penambahan Vitamin E dalam Pakan - Hartandi, Trian; Pebriani, Dewa Ayu Angga; Wijayanti, Ni Putu Putri (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
This study aims to determine the effect of giving vitamin E with different doses in feed on the reproductive condition of female jatimbulan tilapia (Oreochromis niloticus) carried out at the Technical Implementation Unit (UPTD) Freshwater Aquaculture Denpasar Bali. The method used in this study was experimental, using 4 different treatments, namely treatment A (control), treatment B (vitamin E 100 mg/kg), treatment C (vitamin E 150 mg/kg), and treatment D (vitamin E 200 mg/kg) with 3 repetitions. Data were analyzed using One Way ANOVA test, then continued with Duncan's further test using Statistical Package for the Social Sciences (SPSS) software with 95% confidence level (α = 0.05). The total samples observed in this study were 12 female jatimbulan tilapia gonads. The results showed that the provision of vitamin E at a dose of 200 mg/kg feed is the best dose for tilapia gonad maturation, this is because the level of gonad maturity can develop up to TKG V. As well as the value of IKG, fecundity, and fecundity. As well as the value of IKG, fecundity and oocyte diameter are at the optimal amount.